2018
DOI: 10.1007/s10578-018-0839-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Early Life Maltreatment and Maternal History of Depression on Child Psychopathology: Mediating Role of Maternal Sensitivity?

Abstract: The study addresses the impact of maternal early life maltreatment (ELM) and maternal history of depression (HoD) on offspring's mental health. Maternal sensitivity was examined as a potential mediator explaining the relationship between maternal ELM, maternal HoD and child psychopathology. Participants were 194 mothers with and without HoD and/or ELM as well as their children between 5 and 12 years. Maternal sensitivity was assessed using the Emotional Availability Scales. Parent and teacher ratings were util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 86 publications
1
17
0
5
Order By: Relevance
“…The negative practices relaxed discipline and inconsistent punishment may be related to typical manifestations of mood instability of depressive symptomatology, characterizing attitudes of permissiveness and inconsistency that are related to the mother's little involvement. Our study aligns with the findings of Bödeker et al (2019), who identified that maternal depressive symptoms impaired the sensitivity and attention of mothers to their children, and with the statements of Charrois et al (2020) regarding the negative interference of depression in the confidence of mothers in their ability to care for their children, favoring the removal from family routine and the abstention from offering support and affection necessary for the adaptive development of children.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The negative practices relaxed discipline and inconsistent punishment may be related to typical manifestations of mood instability of depressive symptomatology, characterizing attitudes of permissiveness and inconsistency that are related to the mother's little involvement. Our study aligns with the findings of Bödeker et al (2019), who identified that maternal depressive symptoms impaired the sensitivity and attention of mothers to their children, and with the statements of Charrois et al (2020) regarding the negative interference of depression in the confidence of mothers in their ability to care for their children, favoring the removal from family routine and the abstention from offering support and affection necessary for the adaptive development of children.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding family relationships, maternal parental practices make up a continuum of complex behaviors and may have different effects on the children. Generally, two sets of practices stand out, those considered positive for favoring the development of the children and functioning as protection mechanisms, including practices of affection (displays of affection, appreciation, and praise), sensitivity (interest and responsiveness to the child's needs), and positive discipline (monitoring) (Bödeker et al, 2019); and those considered negative because they associate with more problems and fewer resources for the children, including psychological aggression (screaming, threatening, and swearing) (Kuckertz, Mitchell, & Wiggins, 2018), physical and psychological abuse (Wolford, Cooper, & McWey, 2019), and authoritarianism (Calzada, Sales, & O'Garaa, 2019). Concerning depression, mothers have been considered more aggressive (Kuckertz et al, 2018) and less sensitive (Bödeker et al, 2019), and the maternal depressive symptomatology affects negatively on the children's behavior (S.H.…”
mentioning
confidence: 99%
“…Consistent with this theory, there is evidence of the intergenerational effects of ACE exposures (9)(10)(11)(12). In previous studies, maternal exposure to childhood maltreatment and trauma was associated with elevated offspring psychopathology in adolescents as well as in children as young as 36 months, often with evidence that maternal factors, including depression, further influenced childhood risk (13)(14)(15)(16)(17)(18). Beyond maltreatment, studies using broader definitions of early-life adversity provide further support for elevated intergenerational risk.…”
mentioning
confidence: 72%
“…It has been demonstrated to correlate well with child psychiatric diagnoses in children, and thus to provide a valid indicator for mental health problems in children (Kasius et al ., 1997; Jensen and Watanabe, 1999). The high correlation between the internalizing and the externalizing scales on the CBCL in the present study ( r = 0.62, p < 0.001) indicates that the use of the total problem score did not result in undue aggregation of divergent information (Burt et al ., 2005; Bödeker et al ., 2018). However, to provide a more comprehensive picture of different aspects of child psychopathology, details on the results for the two main subscales (internalizing and externalizing behavior) and the more differentiated subscales (e.g.…”
Section: Methodsmentioning
confidence: 99%